Hospital Tariff Gap With Final Claims in The Indonesian Case Base Groups (INA-CBGs) System - Warsi Maryati; Indriyati Oktaviano Rahayuningrum; Vega Nevi Astuti (Proceeding of International Conference on Science, Health, And Technology, 2019)
National Health Insurance is a health program organized by the Social Security Organizing Agency with a prospective payment system or package system. Payment for health services with this package system is based on a diagnosis and procedure grouping that has similar resource needs. This study is an analytical study by examining differences in hospital tariff with final claims on the INA-CBG system. Data collection was carried out by observing 100 INA-CBGs claim files in five hospitals in Central Java Province, Indonesia. Data were analyzed by Paired Sample T-test. The results of the study showed that there was a significant difference with p value < 0.001. The total hospital tariff is IDR 582,373,996.00 compared to the total claim rate in the INA-CBG system of IDR 526,431,595.00, resulting in a negative difference of IDR 55,942,371.00. The difference in tariffs reached 9.6% of the total hospital tariff. The percentage of negative difference between hospital tariff and the tariff in the INA-CBGs system is 53%, slightly more than the 47% positive difference. Most hospitals already have efficient health service management by referring to the established clinical pathway. Financial management with cross subsidies between cases with positive and negative tariff differences can help hospital operations to continue to run well. Compliance of health workers with clinical pathways and effective and efficient management of health services can help hospitals overcome losses in the National Health Insurance system.